IMPLEMENTASI PROGRAM GERAKAN LITERASI SEKOLAH DI SDN SUMURWELUT III/440 SURABAYA - TRI WIBISONO, YANUAR; PANDU PAKSI, HENDRIK (PGSD FIP UNESA, 2018)
The purpose of this study was to find the implementation of the School Literacy Movement program in SDN Sumurwelut III / 440 Surabaya . Tthis studys using a descriptive method. In data collection researchers used several actions namely interviews, observation, and documentation study. The conclusion of this study is that the implementation of the School Literacy Movement program in SDN Sumurwelut III / 440 Surabaya is in accordance with the circular letter from the Surabaya City Government and the Ministry of Education and Culture.In the implementation of literacy programs in schools there are also several obstacles such as insufficient number of books and the absence of library officers other than the city government.But this can be overcome by the way students do reading activities in groups and appoint teachers as library officers. Keywords: Implementation, Program, Literacy Movement, Elemtary School